2017
DOI: 10.1038/s41598-017-08498-6
|View full text |Cite
|
Sign up to set email alerts
|

Association between fasting glucose and all-cause mortality according to sex and age: a prospective cohort study

Abstract: The association of fasting glucose with the risk of death according to sex and age remains unclear, and insufficient information is available on sex- and age-specific glucose concentrations within ethnic groups. This study analyzed a sample of 12,455,361 Korean adults who participated in health examinations during 2001–2004, and were followed up until 2013. Men had 3.0 mg/dL (0.167 mmol/L) higher mean glucose concentrations than women (94.7 vs. 91.7 mg/dL), although women over 73 years had higher levels. For g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
54
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(69 citation statements)
references
References 33 publications
(27 reference statements)
6
54
1
1
Order By: Relevance
“…A priori , we calculated that a total sample size of 48 would have an 80% power to demonstrate between‐group differences in the absolute values of fasting plasma glucose of 0.5 mmol/L, with a standard deviation of 0.4 mmol/L and the AG ratio of 0.05 with a standard deviation of 0.06 at the significance level of 5%. The threshold of a meaningful between‐group difference in fasting plasma glucose was based on the clinical judgement of the author group . To allow for a dropout rate of 20%, a total of 58 patients were randomized.…”
Section: Methodsmentioning
confidence: 99%
“…A priori , we calculated that a total sample size of 48 would have an 80% power to demonstrate between‐group differences in the absolute values of fasting plasma glucose of 0.5 mmol/L, with a standard deviation of 0.4 mmol/L and the AG ratio of 0.05 with a standard deviation of 0.06 at the significance level of 5%. The threshold of a meaningful between‐group difference in fasting plasma glucose was based on the clinical judgement of the author group . To allow for a dropout rate of 20%, a total of 58 patients were randomized.…”
Section: Methodsmentioning
confidence: 99%
“…A meta‐analysis of 102 prospective studies reported that baseline FBG levels between 5.6 mmol/L and 6.9 mmol/L were associated with higher risk of coronary heart disease . Further, some cohort studies in Asia observed that higher glucose levels, even within the normal range, were associated with higher risk of mortality or CVD . Meanwhile, in a recent analysis of seven cohorts in the United States, an FBG level of 6.2 to 6.9 mmol/L was associated with an increased risk of CVD among men, but not women .…”
Section: Discussionmentioning
confidence: 99%
“…2 Further, some cohort studies in Asia observed that higher glucose levels, even within the normal range, were associated with higher risk of mortality or CVD. 12,13 Meanwhile, in a recent analysis of seven cohorts in the United States, an FBG level of 6.2 to 6.9 mmol/L was associated with an increased risk of CVD among men, but not women. 14 In the present study, impaired FBG, even within levels 5.6 to 6.0 mmol/L, was associated with poor outcomes, irrespective of age or sex, while the associations were more apparent in adults of normal weight than in overweight adults ( Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, there has been crescent interest in developing non–insulin‐based IR indexes including the TyG index and TG/HDL‐C ratio. Components of such indices, including fasting glucose, triglycerides, and HDL‐C, have been shown predictive of hypertension and CV risk in prospective studies . A significant contribution of hypertension and CVD risk is explained by arterial stiffness, which implies degeneration of elastin fibers and deposition of collagen in arterial walls, inducing structural and functional modifications in the arterial wall .…”
Section: Introductionmentioning
confidence: 99%
“…Components of such indices, including fasting glucose, triglycerides, and HDL-C, have been shown predictive of hypertension and CV risk in prospective studies. [5][6][7] A significant contribution of hypertension and CVD risk is explained by arterial stiffness, which implies degeneration of elastin fibers and deposition of collagen in arterial walls, inducing structural and functional modifications in the arterial wall. 8 The TyG index and the TG/HDL-C ratio have proven strong and consistent associations with hypertension, CVD risk, and arterial stiffness in several populations, suggesting a potential role for IR assessment in identifying arterial stiffness using non-insulin-based IR surrogates.…”
Section: Introductionmentioning
confidence: 99%